Bilateral lateral rotation of the kidneys with their hilum facing laterally (outwards) - Rare anatomical variations - Gopinath, Vinu; Mookambika, RV; Nair, Velayudhan; Nair, Rema V; Mohandas Rao, KG (Asian Journal of Medical Sciences, 2015)
Among the variations of the renal system, abnormalities of structure and position of kidney along with the variations of renal vessels are reported most frequently. However, reports on rotational abnormalities and abnormal positions of renal hilum are scanty. During routine dissection of the posterior abdominal wall, laterally rotated kidneys with laterally facing hila were observed in about 60-year-old male cadaver. On right side, the hilum was more on the anterior surface of the organ and right renal vein was emerging almost from the middle of the anterior surface at the lateral edge of the hilum. However, the hilum of the left kidney was observed along the lateral border of the organ and left renal artery was crossing transversely anterior to the kidney forming a loop to reach the hilum. It was also observed that because of the lateral position of the hilum, the renal vessels and pelvis where passing over the anterior surface of the kidney. Rotational variations and abnormal locations of renal hilum are of importance in surgical procedures like percutaneous nephrectomy. Further clinical and surgical importance of the case is discussed in the paper. DOI: http://dx.doi.org/10.3126/ajms.v6i5.12414 Asian Journal of Medical Sciences Vol.6(5) 2015 82-84